The Incredibles (Disney Movie Collection: A Special Disney Storybook Series, 2015)
When Bob Parr, a.k.a. Mr. Incredible, gets called out of retirement for a top-secret mission, his family of superheroes including his wife Helen (a.k.a. Elastigirl) and his children Violet, Dash, and Jack-Jack need to ban together to rescue the world from total destruction. Can this Super family overcome the wicked plot of Syndrome in time? Enjoy this exclusive large-size Disney Pixar movie storybook of The Incredibles, featuring beautifully illustrated pages fans can treasure for years to come.